What Influences the Sustainable Food Consumption Behaviours of University Students? A Systematic Review - Lucía Aguirre Sánchez; Lucía Aguirre Sánchez; Zayne M. Roa-Díaz; Zayne M. Roa-Díaz; Magda Gamba; Magda Gamba; Giorgia Grisotto; Giorgia Grisotto; Giorgia Grisotto; Ana Maria Moreno Londoño; Blanca Patricia Mantilla-Uribe; Alba Yaneth Rincón Méndez; et al. (Frontiers Media S.A., 2021)
Objectives: Global environmental challenges demand sustainable behaviours and policies to protect human and planetary health. We aimed to summarize the evidence about the factors related to Sustainable Food Consumption (SFC) behaviours of university students, and to propose an operational categorization of SFC behaviours.Methods: Seven databases were searched for observational studies evaluating Sustainable Food Consumption (SFC) among university students and that reported at least one behavioural outcome measure. Qualitative synthesis was conducted, and PRISMA guidelines for reporting were followed.Results: Out of 4,479 unique references identified, 40 studies were selected. All studies examined personal factors, while 11 out of 40 also measured social or situational factors. Except for food waste, females had higher levels of SFC behaviours, but situational factors moderated this association. Knowledge and attitudes showed mixed results. Overall, sustainable food consumers reported healthier lifestyles.Conclusions: Healthy lifestyle of sustainable food consumers suggests possible synergies between human health and sustainability in terms of motivations for food choice. Moderation effects of social and situational factors on personal factors reveal opportunities to design and examine the effects of choice architecture interventions.